DETERMINATION OF MARKER OF THE ACUTE PHASE OF INFLAMMATION IN PATIENTS WITH ODONTOGENIC PHLEGMONS ON THE BACKGROUND OF ISCHEMIC HEART DISEASE - Lokes, K.P.; Kiptilyi, A.V.; Yatsenko, I.V.; Steblovskyi, D.V.; Boyko, I.V.; Yatsenko, P.I.; Avetikov, D.S. (World of Medicine and Biology, 2023)
One of the factors that can influence the clinical course of odontogenic phlegmons is ischemic heart disease, which is quite common among patients of maxillofacial departments. It was noted the significant increase in the content of C-reactive protein in blood serum all clinical groups on the first day of observation. During the entire period of observation, a gradual and reliable decrease in the content of this indicator was observed in all studied clinical groups. The best results were observed in patients of the control group, as well as in patients with odontogenic phlegmons against the background of ishemic heart disease, who were treated conservatively with quercetin in combination with 2-ethyl-6-methyl-3-hydroxypyridine succinate, which indicates a positive therapeutic effect of the combination of these drugs on the course of purulent-inflammatory processes of maxillofacial localization in patients with ischemic heart disease.
Keywords: odontogenic phlegmone; ishemic heart disease; biochemical marker; surgical treatment